2020
DOI: 10.1186/s40959-020-00066-8
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of doxorubicin cardiotoxicity by early detection of subclinical right ventricular dysfunction

Abstract: Background: Doxorubicin remains one of the most common causes of cardiotoxicity in patients with lymphoma, leading to significant morbidity and mortality. Early decline in left ventricular (LV) ejection fraction predicts chemotherapy-induced cardiotoxicity and mortality, but limited data exist on doxorubicin-induced subclinical right ventricular (RV) dysfunction. We investigated dose-dependent subclinical doxorubicin-induced RV dysfunction in lymphoma patients. Methods: Thirty-five patients with adult lymphoma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 23 publications
1
17
2
Order By: Relevance
“…Furthermore, subclinical differences in RV systolic EF and end-systolic volumes at baseline predicted LV systolic dysfunction after anthracyclines. These findings are consistent with recent reports that the RV may be at least as vulnerable to injury from anthracyclines as the LV, and early RV dysfunction may predict anthracycline-induced cardiotoxicity 16 , 17 . In addition, the reproducibility analysis for the RV ECV, demonstrated that our measurements were reliable, consistent and reproducible with ICC coefficients > 0.75 26 .…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Furthermore, subclinical differences in RV systolic EF and end-systolic volumes at baseline predicted LV systolic dysfunction after anthracyclines. These findings are consistent with recent reports that the RV may be at least as vulnerable to injury from anthracyclines as the LV, and early RV dysfunction may predict anthracycline-induced cardiotoxicity 16 , 17 . In addition, the reproducibility analysis for the RV ECV, demonstrated that our measurements were reliable, consistent and reproducible with ICC coefficients > 0.75 26 .…”
Section: Discussionsupporting
confidence: 93%
“…There are a paucity of studies applying such tissue characterization techniques to better understand the effects of anthracyclines on the RV. This is in contrast to several published studies on LV tissue remodeling after anthracyclines 2 5 ; additionally, several studies 16 , 17 have suggested that the RV may be more vulnerable to injury from anthracyclines, and early RV dysfunction may predict anthracycline-induced cardiotoxicity. We were specifically interested in understanding the effects of anthracyclines on the RV fibrosis, as measured by calculation of the extracellular volume (ECV), and on cardiomyocyte mass.…”
Section: Introductioncontrasting
confidence: 94%
See 1 more Smart Citation
“…Betanin is a glycosidic water-soluble red pigment and is the bioactive constituent of red beetroot. [20][21][22][23] Its consumption has several health benefits, such as protection against ventricular disruption and ischemic injury [24,25]. Allicin (diallyl thiosulfate) is a major constituent of garlic [26][27][28][29].…”
Section: Introductionmentioning
confidence: 99%
“…The data on RV strain in CTRCD suggests RV dysfunction frequently occurs with LV dysfunction and pertains a reduced recovery in LV function, though further studies are needed (26). Additionally, other studies suggest 2D and 3D RV strain deterioration occurs prior to LV parameters (27,28).…”
Section: Right Ventriclementioning
confidence: 98%